Influence Competencies, Job Training, Self Efficacy And Career Development On Employee Performance With Job Satisfaction As An Intervening Variable At PT Thong Langkat Energi - Prilia Sona Br Ginting; M. Chaerul Rizky (International Journal of Management, Economic and Accounting, 2025)
Employee performance and job satisfaction are two factors that are closely related and have a crucial role for PT Thong Energi Langkat, where a high level of job satisfaction will encourage employees to give their best performance so that they can increase the company's overall productivity. This study aims to analyze the influence of competence, job training, self-efficacy, and career development on employee performance with job satisfaction as an intervening variable at PT Thong Langkat Energi. The problem behind this study is that there are indications of declining employee performance that need to be identified as the causative factors. The research used is quantitative research with an associative approach. The data collection method was carried out through the distribution of questionnaires to respondents using the Likert scale 1-5. The population in this study is all employees of PT Thong Langkat Energi totaling 50 people, with a sampling technique using the census method so that the entire population is used as a research sample. The data used is primary data obtained directly from respondents through questionnaires and secondary data from company documentation. The data analysis technique uses Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach through SmartPLS software. The results of the study show that job satisfaction does not have a significant influence on employee performance. Competence has a significant effect on job satisfaction, but does not have a significant effect on employee performance. Job training has a significant influence on job satisfaction, but not on employee performance. Career development has no significant influence on either job satisfaction or employee performance. Self-efficacy does not have a significant effect on job satisfaction, but it does have a significant effect on employee performance. In addition, job satisfaction is not able to mediate the relationship between competence, job training, career development, and self-efficacy on employee performance.